Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The degree of impact of the admission policies of Jordanian public universities in aligning their outputs with the requirements of the labor market from the point of view of the facultyDr. Nisreen Abd Alhafed Alofishat2. Reality of remote Training in light of the Corona pandemic from the male and female teacher's point of view at Riyadh and DammamDr. Abdullah Mohmmad Al-Shaye, Mrs. Afnan Ali Mohmmad Al-Wadey3. Parental treatment methods and their relationship to achievement motivation among a sample of gifted female students at the secondary stage in JeddahMrs. Maram Hajjaj Al- Mabadi, Dr. Manal Yahya BaAmer4. Methods of access for people with intellectual disabilities to public education curricula and the factors affecting them from the point of view of teachers in Al-Jouf regionMrs. May Farzal Alshammari, Dr. Maha Saud Albulayhid5. Emotional Eating- Theoretical FrameworkMrs. Rasha Mohammed Alshehri, Prof. Sabah Alrefae, Asst-Prof. Arwa Alkhalaf6. Islamic texts refer to psychosomatic illnesses Historical comparisonMr. Faisal Qasem Aloshari
Keywords: Journal of Educational and Psychological Sciences